Controlling DNA Translocation Through Solid-state Nanopores - Yuan, Zhishan (Nanoscale Res Lett, 2020)
Compared with the status of bio-nanopores, there are still several challenges that need to be overcome before solid-state nanopores can be applied in commercial DNA sequencing. Low spatial and low temporal resolution are the two major challenges. Owing to restrictions on nanopore length and the solid-state nanopores’ surface properties, there is still room for improving the spatial resolution. Meanwhile, DNA translocation is too fast under an electrical force, which results in the acquisition of few valid data points. The temporal resolution of solid-state nanopores could thus be enhanced if the DNA translocation speed is well controlled. In this mini-review, we briefly summarize the methods of improving spatial resolution and concentrate on controllable methods to promote the resolution of nanopore detection. In addition, we provide a perspective on the development of DNA sequencing by nanopores.